2016
DOI: 10.1007/s10633-016-9558-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of photopic negative response measurements in the time and time–frequency domains

Abstract: Purpose To compare measurements of the full-field photopic negative response (PhNR), as well as intra-subject variation in the PhNR, using time and time-frequency domain analyses. Methods Full-field ERGs were recorded from 20 normally-sighted subjects (ages 24 to 65 years) elicited by a long-wavelength pulse (3 cd s m−2) presented against a short wavelength adapting field (12.5 cd m−2). Three to 10 waveforms were obtained from each subject and each waveform was analyzed using standard time domain analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In electrophysiology of vision, this method has been introduced a decade ago [ 20 , 21 ]. It has been used to analyze the photopic negative response in the full-field ERG of healthy subjects [ 22 ]. Barraco et al [ 23 ] compared different analytical approaches (including application of the continuous wavelet transform, CWT) to analyze the a -wave of the full-field ERG, demonstrating consistently altered photoreceptor behavior in various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In electrophysiology of vision, this method has been introduced a decade ago [ 20 , 21 ]. It has been used to analyze the photopic negative response in the full-field ERG of healthy subjects [ 22 ]. Barraco et al [ 23 ] compared different analytical approaches (including application of the continuous wavelet transform, CWT) to analyze the a -wave of the full-field ERG, demonstrating consistently altered photoreceptor behavior in various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The DWT generates scalograms (Figure 1(a)) which display the energy ( z -axis) of the signal (maximal values are shown in red; lowest values in blue) as a function of time ( x -axis) and frequency ( y -axis). As previously demonstrated by us and others [10, 13, 1518], this time-frequency approach allows for the identification of energy descriptors, each defined with their respective time and frequency coordinates. The DWT yields measurements of the photopic b-wave (found in the 20 and 40 Hz bands) and OPs (found in the 80 and 160 Hz bands) through the quantification of their respective associated wavelet coefficients [10, 16, 17].…”
Section: Methodsmentioning
confidence: 90%
“…Unfortunately, given that the FFT quantifies the power level of all the frequency components contained within a signal (such as the ERG), whether they are time-locked to the stimulus or not (i.e., no temporal resolution), its use can lead to erroneous interpretations [10, 13–15]. Fortunately, the latter limitation can be easily overcome with the use of the discrete wavelet transform (DWT), which is somewhat of an improved FFT since it includes both temporal and frequency resolutions [10, 13–18]. …”
Section: Introductionmentioning
confidence: 99%
“…Baseline trend correction requires a compromise between trend removal, which improves signal repeatability, and waveform distortion which reduces discriminatory ability. Using discrete wavelet analysis, Kundra et al 22 showed that the PhNR was characterized by components located near the 11 Hz band (approximate range, 8–16 Hz), with minor contribution from lower frequencies (approximate range, 2–8 Hz). Thus, setting a high pass above 2 Hz attenuated the PhNR by removing these lower frequencies ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The PhNR was shown to contain low temporal frequencies near approximately 11 Hz with smaller contributions from frequencies in the 2 to 8 Hz range. 22 Therefore, a comparison of increasing the high-pass cutoff from 1 to 10 Hz (in 1 Hz increments) was evaluated. The ISCEV low-pass cutoff of 300 Hz was retained.…”
Section: Methodsmentioning
confidence: 99%